2D ultrathin carbon nanosheets derived from interconnected Al-MOF as excellent hosts to anchor selenium for Li-Se battery - Jin, Wen-Wu; Li, Hejun; Zou, Jizhao; Inguva, Saikumar; Zhang, Qi; Zeng, Shao-Zhong; Xu, Guozhong; Zeng, Xierong (Elsevier, 2019)
Alleviating volume expansion of the electrodes and improving utilization of the active materials have become key problems restricting a successful commercialization of lithium-selenium batteries. In this paper, a 2D ultrathin carbon nanosheets derived from interconnected MOF is designed for the first time. Such carbon nanosheets are composed by parallel stacked 2D sub-units, and this unique hierarchical porous architecture is beneficial for buffering the volume expansion and for improving the utilization rate of the active materials. Therefore, the cathode displays an excellent cycling stability with a reversible capacity of 347.3 mAh g−1 at 2 C after 240 cycles.
Keywords: Carbon materials; structural; 2D-MOF; interconnected; Li-Se